Physical and Psychological Violence in Dating with Sleep Duration of Adolescents in Bantul Regency - Suci Musvita Ayu; Liena Sofiana; Dina Ayu Martantika; Erni Gustina (Universitas Ahmad Dahlan, 2021)
Background: The trend of juvenile delinquency, especially Dating Violence (DV) is still very high. According to the Annual Records (Catahu), there were 2,073 cases in 2018. The Special Region of Yogyakarta ranked sixth as region with the highest DV cases in Indonesia, reaching 980 cases in 2018. In Bantul Regency, 80 cases were reported in 2018. Dating violence can have negative impact on the physical and psychological well-being of adolescents. Physical violence can lead to bruises and fractures while psychological violence affects the victims in the form of depression, stress, anxiety and sleep disturbances. This study aims to analyze the relationship between physical and psychological violence in dating with sleep duration of adolescents. Method: This research used quantitative research method with a cross sectional approach. Data were analyzed using chi square. The sample consisted of 314 high school students (15-19 years old) who were recruited using purposive sampling technique. Only subjects who have dated or are currently dating were included in this study. Results: The results showed that there was a relationship between physical violence in dating and sleep duration (PR = 1,165; 95% CI = 1,050-1,293; p<0.05). However, there was no relationship between psychological violence in dating and sleep duration (PR = 1,068; 95% CI = 0,957-1,192; p>0.05). Conclusion: The results suggest that there is a relationship between physical violence in dating and sleep duration. Teenagers are advised to take advantage of the PIK-R program at school or visit counseling teachers that can help them solving their problems.